The art of lyric writing: the metaphor and its effective usage / Liyana Yis - Yis, Liyana (2010)
Lyric writing could be defined as the art of expressing feelings through words. Figurative language is a principal of saying things in a different perspective, an important device used in lyric writing. There are many types of figurative language, as much as its different character and rules of application in lyric writing. This study covers the effective usage of metaphor, an umbrella term for types of figurative language, in lyric writing. There are also explanations on the idea of creating metaphor and its application guideline in lyric writing. Discussions and comparisons of existence work that relates to the usage of the metaphor were also being provided in this study. By generating a better understanding of the effective usage of the metaphors, this study benefits lyricist, researchers and anyone who wants to learn this skill in more depth, help them to produce a good piece of art work, the quality lyrics.